A Cost Evaluation of the Georgia Stroke and Heart Attack Prevention Program - Rosanne Farris, PhD, RD; J. Nell Brownstein, PhD; Patricia Jones, RN, CDE; Hong Chen, MS; Diane Orenstein, PhD; David B. Rein, PhD; Roberta T. Constantine, PhD (Centers for Disease Control and Prevention, 2006)
IntroductionHypertension is a leading cause of stroke, coronary artery disease, heart attack, and heart and kidney failure in the United States, all of which contribute to the rising costs of health care. The Georgia Stroke and Heart Attack Prevention Program is an education and direct service program for low-income patients with hypertension. This project evaluated the cost-effectiveness of the program compared with the following two alternative scenarios: no treatment for high blood pressure and the typical hypertension treatment received in the private sector nationwide (usual care).MethodsWe estimated the preventive treatment costs and number of adverse health events averted (hemorrhagic and ischemic stroke, heart disease, and kidney failure) associated with the Georgia Stroke and Heart Attack Prevention Program in two Georgia health districts. We used program cost and service usage data obtained from the Georgia Department of Human Resources and probabilities and costs of expected adverse events published in peer-reviewed sources. We compared program costs and number of expected adverse health events averted with those expected from 1) no preventive care and 2) usual care for high blood pressure.ResultsThe Georgia Stroke and Heart Attack Prevention Program was less costly and resulted in better health outcomes than either no preventive care or usual care. Compared with no preventive care in the two districts, the program was estimated to result in 54% fewer expected adverse events; compared with usual care, the program was estimated to result in 46% fewer expected adverse events. Combining the costs of preventive treatment with the costs of expected adverse events, the Georgia Stroke and Heart Attack Prevention Program cost an average of $486 per patient annually, compared with average annual costs of $534 for no care and $624 for usual care.ConclusionMaintaining a publicly financed stroke and heart attack prevention program is more cost-effective and results in greater health benefits than other plausible scenarios. Because the benefits of this program accrue to both the state and federal governments through reduced Medicaid and indigent care expenditures, both the state and federal governments have a financial incentive to support the program.